Witnessing the testing of the first Soviet electric plough at the experimental farm of the Moscow Higher Zootechnical Institute (Butyrsky Khutor). Compare: 69/39 A, page 350-351 - Zubkov, F.,
Witnessing the testing of the first Soviet electric plough at the experimental farm of the Moscow Higher Zootechnical Institute (Butyrsky Khutor). Compare: 69/39 A, page 350-351.